(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The marine deposits of the Río Mayer Formation are part of the initial filling of the Austral Basin, which is developed in the southernmost part of South America, including the south of Chile and Argentina (southwestern Patagonia, Santa Cruz and Tierra del Fuego Provinces, Figs. 1, 2). The study area is located between the San Martín and Argentino lakes in the Santa Cruz Province (Fig. 3). The Río Mayer Formation (Fig. 2) was studied in three main localities, where detailed sedimentary logging was undertaken (Figs. 4, 5), taking into account the lithology, the primary sedimentary structures, the palaeontological content, rock bodies geometry, their orientation and the hierarchy as well as the contacts with underlying and overlying units. Eighteen sedimentary facies were defined (Figs. 6, 7; Table 1), which were grouped into three facies association representing different sedimentary palaeoenvironments, like marine outer platform (AF 1), marine outer platform influenced by a deltaic system (AF 2) and prodelta (AF 3) (Fig. 8, Tables 1, 2). The facies of the outer platform palaeoenvironment corresponds to the rocks traditionally assigned to the Río Mayer Formation, according to the available bibliography, and deposited by hemipelagic and authigenic processes interrupted by episodic sedimentation. The deposits of the outer platform influenced by a deltaic system palaeoenvironment are similar to the above mentioned but presents continental fossils that indicate a deltaic source. Finally, AF 3 of a prodelta palaeoenvironment is dominated by sandy/heterolithics levels associated with turbidity currents and hyperpycnal flows originated in a delta front. The best and most complete exposures of the unit were observed in the Río Guanaco locality, where palaeoenvironmentalinterpretationswereperformed, allowing the division of the 350 m-thick unit in three sections (Fig. 9). The lower section is composed mainly by black shales with both tabular and concretional marls levels (AF 1). Trace fossils are not recorded in this section, but ammonites, belemnites and bivalves are frequent. It has been interpreted as accumulated in a distal platform, under anoxic conditions. The middle section is characterized by bioturbated black marls and shales, with well- preserved Zoophycos ichnofacies (Richiano et al., in press), occurring in a distal platform depositional environment. Body fossils are frequent, especially belemnites. The upper section is composed of massive black mudstones with intercalations of very fine- to fine-grained sandstones and less frequent conglomerates. In this section both debris flows and distal low-density turbidity current deposits were identified. Zoophycos ichnofacies and Ophiomorpha rudis ichnosubfacies were recognized in association with molds of petrified wood containing Teredolites isp. (Richiano et al., in press). The presence of turbulent currents and large trace fossils suggest a more oxygenated conditions. At Lago San Martín and Estancia La Vega localities the most significant characteristic is the presence of prodeltaic deposits in the transition between Río Mayer Formation and Piedra Clavada formations (Fig. 9). To sum up, after the Upper Jurassic rifting stage of the Austral Basin, the Springhill Formation represents the initial infill of the extensional structures. After that, during the Berriasian (Fig. 10a), the levels of the lower section of the Río Mayer Formation started to accumulate in the Río Guanaco area. During the Valanginian (Fig. 10b), an acceleration in the transgression generated the accumulation of the Springhill Formation in the Lago San Martín area while in the Río Guanaco region the middle section of the Río Mayer Formation developed. Between the Hauterivian and the Barremian all the study area was under distal platform conditions (Fig. 10c). A major change in the sedimentary systems of the Austral Basin during the Lower Cretaceous is the development of the deltaic Piedra Clavada Formation (Fig. 10d). This event generated two different palaeoenvironments in the Río Mayer Formation. Prodeltaic deposits are present to the north, while sediments of distal platform conditions with highly frequent sandy levels prevail southwards. Finally a new transgression indicates the beginning of the Cerro Toro and Mata Amarilla formations in the middle Albian- lower Cenomanian (Fig. 10e).